Peran Kecakapan Manajerial dan Koneksi Politik terhadap Praktik Manajemen Laba Dimoderasi Tata Kelola Perusahaan - Saraswati, Ade Maya; Albab, Farah Nisa Ul (Jurnal Akuntansi dan Governance, 2024)
Objectives: This research aims to examine the influence of managerial ability and political connections on earnings management practices moderated by corporate governance.Design/method/approach: Quantitative method, secondary data source energy sector listings on the IDX for 2019-2022 using purposive sampling and panel data regression analysis with the E-views program.Results/findings: Managerial ability have a negative influence on earnings management, political connections have a positive influence on earnings management, corporate governance strengthens the relationship between managerial ability and earnings management, and corporate governance weakens the relationship between political connections and earnings management.Theoretical contribution: Research can enrich the literature, deepen understanding, and help develop more comprehensive theoretical models regarding the mechanisms and motivations earnings managementPractical contribution: Companies need to increase transparency in financial reporting and commit to accountability, companies need to evaluate risks related to political connections, and create strategies to manage or minimize these risks.Limitations: The limitations of this research are the variability of managerial styles and the lack of internal data political connections are difficult to measure due to diverse political interests. In corporate governance, there are differences in standards between countries and overall limitation terms of period time.